Perspectives on Underlying Factors for Unhealthy Diet and Sedentary Lifestyle of Adolescents at a Kenyan Coastal Setting - Ssewanyana, Derrick; Abubakar, Amina; van Baar, Anneloes; Mwangala, Patrick N.; Newton, Charles R. (Frontiers in Public Health, 2018)
Unhealthy diet and physical inactivity are among the four key modifiable risk factors for non-communicable diseases such as diabetes and cardiovascular disease. These behaviors are typically initiated or reinforced during adolescence. However, knowledge on underlying factors for adolescents’ unhealthy dieting and physical inactivity in sub-Saharan Africa is poor. We conducted in-depth interviews and focus group discussions to explore the perceptions of 85 young people and 10 stakeholders, such as teachers, clinicians and staff from organizations at the Kenyan coast on: (a) adolescents’ unhealthy food choices and their forms of sedentary behavior; (b) predisposing factors; and (c) protective factors against unhealthy food choices and sedentary behavior of adolescents living in Kilifi County. The findings reveal that adolescents occasionally access nutritious foods like fruits, vegetables and animal protein. However, there is a growing tendency to consume unbalanced diets with high intake of carbohydrates, oily foods and consumption of sugar dense processed foods and drinks. Sports and domestic chores were found to be major sources of physical activity. Sedentary lifestyles characterized by a long time sitting and chatting, watching sports games and movies were described. Using a Socio-Ecological model, our findings suggest that risk factors are numerous and inter-related, especially at intrapersonal, interpersonal and community level. The negative influencers at an intrapersonal level were: body image concerns, attitudes and misconceptions, substance use behavior, and taste for unhealthy foods.. In the interpersonal domain, household poverty and parenting practices that condone unhealthy habits were identified risk factors. Availability of affordable unhealthy foods, high prices for nutritious food, farming practices, gambling, and influx of transportation alternatives in the community were interrelated but also had relationships with intrapersonal and interpersonal risk factors. Modernization and poor implementation of policies were discussed as predisposing factors especially by stakeholders from a societal perspective. Seasonality and farming practices, school attendance, community-based services, and policy and regulations on idleness were identified as potential protective factors. Our findings provide a unique qualitative insight of the factors underlying adolescents’ dietary and sedentary lifestyle and highlight the need for ecological intervention approaches to address these forms of health risk behavior in a rural African setting.